(untitled) - 1950-; Quaid, Randy; 1958-; Colin, Margaret; Rebhorn, James; 1948-2014; Fierstein, Harvey; 1952-; Loggia, Robert; Hirsch, Judd; Devlin, Dean; Emmerich, Roland; et al. (Beverly Hills, California, 2013)
Spaceships appear and wonder turns to terror as they attack cities all over the Earth.
MPAA rating PG-13.
CHV rating: PG.
Keywords: Space warfare; Dialogues, French; Human-alien encounters; Space warfare; Drama; Human-alien encounters; Drama; Films for the hearing impaired; Fiction films; Science fiction films; Feature films; Video recordings for the hearing impaired; War films; Drama; Video recordings; Drama; Action and adventure films; War films; Feature films; Science fiction films; Fiction films; Video recordings for the hearing impaired; Films for the hearing impaired; Action and adventure films